The Optimization Application of Clean and Healthy Living Behavior at TK Negeri Pembina West Rengat - Nina Selvia Artha; Yulianto Yulianto (Poltekkes Kemenkes Riau, 2023)
Health is an important part for everyone to be able carry out activities. The concept of healthy living which is reflected in healthy behavior needs to be introduced as early as possible to the next generation and then internalized and practiced. Students are no longer solely as objects of health development but as subjects and thus it is hoped that they can play a conscious and responsible role in health development. The purpose of this community service is to optimize clean and healthy living behavior at TKN Pembina Rengat Barat. The target of this community service is 26 students of the State Kindergarten of Pembina Barat Rengat Barat. This activity was carried out 5 times while the implementation of each activity was the first meeting of the pretest followed by the PHBS snake and ladder game, the second meeting of washing hands properly using soap and running water, the third meeting of education about healthy food, the fourth meeting of education and the practice of disposing of waste. which is correct and the last is a post-test to see how far the participants' knowledge about PHBS has increased. The result of this community service activity is that there is an increase in the knowledge and skills of participants, this can be judged by the results of the pre-test knowledge level of the majority of the category less than 19 people (73.1%). Meanwhile, the post-test results showed that the majority of knowledge was good, is 14 people (53.8%). Suggestions for the school to always emphasize students to always get used to and carry out clean and healthy PHBS behavior with the aim of making it a habit.